2003
DOI: 10.1002/chin.200352017
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Blinking from Silver Nanostructures.

Abstract: Silver nanostructures deposited on glass showed luminescent blinking when excited at a high 442 nm irradiance. The irradiance required to photoactivate the silver, was dependent on the nature of the silver nanostructures. Silver fractal-like structures were found to be highly emissive, requiring only ≈30 W/cm 2 for photoactivation as compared to silver island films and spin-coated silver colloids, which required a significantly higher irradiance, > 100 W/cm 2 , to observe similar luminescent emission. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Ensemble NCs in solution are photostable, moreover photoinduced fluorescence enhancement was observed for long-time illumination. This photoinduced fluorescence enhancement has been observed for colloidal CdSe QDs [16][17][18] and silver nanoparticles [19], likely due to photoinduced surface passivation. However, when the solvent was evaporated, fluorescence intensity dropped rapidly with illumination time.…”
Section: Resultsmentioning
confidence: 69%
“…Ensemble NCs in solution are photostable, moreover photoinduced fluorescence enhancement was observed for long-time illumination. This photoinduced fluorescence enhancement has been observed for colloidal CdSe QDs [16][17][18] and silver nanoparticles [19], likely due to photoinduced surface passivation. However, when the solvent was evaporated, fluorescence intensity dropped rapidly with illumination time.…”
Section: Resultsmentioning
confidence: 69%
“…Because each individual cluster displayed an unusually bright emission and was resistant to photobleaching, we next examined whether such properties were a result of metalenhanced emission of ThT or an intrinsic fluorescent property of the silver of the nanoclusters. Silver is known to exhibit bright and photostable fluorescence as was previously shown for gaseous silver particles, silver deposited on surfaces, and silver dots encapsulated into dendrimers, but not for silver in aqueous solutions (3,4,22,23). To address this question we compared the emission spectra collected from an area of view densely populated with nanoclusters to spectra recorded from the fibrils prestained only with ThT.…”
Section: Resultsmentioning
confidence: 99%
“…2 d). Previous studies demonstrated that the agglomeration of noble metals into nanodots and nanocomposites is usually accompanied by the appearance of plasmon absorption, with a maximum between 380 and 600 nm, depending on the size and composition of nanocomposites (3,4,(15)(16)(17). For instance, oligonucleotidebound silver nanoclusters displayed two broad absorption peaks with maxima at 424 nm and 520 nm (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver nanoparticles (NP), clusters and composite nanostructures based on them demonstrate local surface plasmon resonance (LSPR) [1][2][3], luminescence in the visible spectral range [2][3][4][5][6][7][8], photochromism [2], which opens wide possibilities to study distinctive optical properties of nanoparticles as compared to those in bulk objects as well as to use them in various applications from biosensors to informatics and storage devices. Excitation of LSPR results in creation of strong local fields around the nanoparticles, which causes enhancement of Raman scattering, luminescence, optical non-linearity, etc.…”
Section: Introductionmentioning
confidence: 99%